Modula??o codificada sobre m?ltiplas portadoras em canais com m?ltiplos percursos variantes no tempo - Ferreira, Alexandre Carvalho (2008)
The signal transmitted in a digital radio link is submitted to various distortions due to the interferences and noise introduced by the communication channel. Theses distortions can reduce the system performance. Among the factors that contribute to these distortions, one that must be analyzed is the multipath propagation. This kind of propagation may introduce frequency selective fading in the transmitted signal. The aim of this work is to analyze the distortions caused by the multipath propagation in a digital radio link and to estimate the system outage, in the presence of this kind of propagation, in a time variant channel. Two channel's models and a multicarrier scheme with special features for digital radio links are analyzed. Some counter-measures in order to deal with the channel's distortions e?ects, like a block coded scheme, using short codes, and a block interleaving scheme are analyzed either. A digital radio link behaviour analysis in a communication channel with multipath propagation is performed and, once the result of this analysis is achieved, an estimative of the digital radio link outage probability is obtained for a time variant channel.